Compositional evolution of lignite during spontaneous combustion under low-temperature oxidation. Issue 4 (7th June 2021) - Xin, Lin; Xu, Min; Feng, Mingze; Li, Kaixuan; Wang, Zhigang; Xie, Jun; Han, Limin; Liu, Weitao
Abstract : In order to better explore the spontaneous combustion characteristics of lignite, a low-temperature heating experimental device was used to study the changes in the physical and chemical structure of lignite in an air atmosphere of 50–350°C. Through FTIR, XRD and SEM, the coal sample's chemical structure and surface microstructure change at low temperature are correlated and analysed, and the physical and chemical fabric change law of the coal sample at low temperature is obtained. The results show that in the water loss stage, the hydroxyl content in the coal sample increases, and the surface pores of the coal sample become larger. As the oxidation temperature increases, the pores further expand, secondary cracks appear, and gas escapes. In the decarboxylation stage, the coal sample is further coked, the methyl group increases, the oxygen-containing functional group increases, and the coal sample crystallisation degree increases, which accelerates the spontaneous combustion of the coal sample. The result of our study offers useful guide for early coal spontaneous combustion prediction on site.